Operational management of trunk main discolouration risk. Issue 4 (18th May 2016) - Cook, D.M.; Husband, P.S.; Boxall, J.B.
Abstract : Despite significant on-going investment, water companies continue to receive an unacceptable number of discolouration related customer contacts. In this paper, data from intensive distribution system turbidity monitoring and cluster analysis of discolouration customer contacts indicate that a significant proportion of these contacts are due to material mobilising from the trunk main system, and operational flow increases are shown to have a higher discolouration risk than burst incidents. A trunk main discolouration incident highlighting this risk is discussed, demonstrating the need for pro-active trunk main risk assessments. To identify the source of the material event flow rates were modelled using the PODDS (prediction of discolouration in distribution systems) discolouration model. Best practice pro-active management is demonstrated in a case study where the PODDS model is used to implement managed incremental flow changes on a main with known discolouration risk with no discolouration impact to customers and significant cost savings.